2016
DOI: 10.1159/000443706
|View full text |Cite
|
Sign up to set email alerts
|

Epidemiologic Study of Charcot-Marie-Tooth Disease: A Systematic Review

Abstract: Background: Charcot-Marie-Tooth disease (CMT) is the most common inherited neuropathy. CMT is classified into 2 main subgroups: CMT type 1 (CMT1; demyelinating form) and CMT type 2 (CMT2; axonal form). The objectives of this study were to systematically review and assess the quality of studies reporting the incidence and/or prevalence of CMT worldwide. Summary: A total of 802 studies were initially identified, with only 12 meeting the inclusion criteria. CMT prevalence was reported in 10 studies and ranged fro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
151
0
8

Year Published

2017
2017
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 219 publications
(161 citation statements)
references
References 23 publications
2
151
0
8
Order By: Relevance
“…In this population, the proportion of axonal CMT was higher than that of demyelinating CMT, and among the patients with CMT a molecular diagnosis could be made for 55% of the cases. A recent systematic review on the epidemiology of CMT identified 103 potentially relevant studies, but only 12 studies met the inclusion criteria and 10 studies reported on CMT prevalence [20]. Indeed, population-based studies on the epidemiology of inherited polyneuropathies are quite few [14,21,22,23] and many of them preceded the era of modern molecular diagnostics [24,25].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In this population, the proportion of axonal CMT was higher than that of demyelinating CMT, and among the patients with CMT a molecular diagnosis could be made for 55% of the cases. A recent systematic review on the epidemiology of CMT identified 103 potentially relevant studies, but only 12 studies met the inclusion criteria and 10 studies reported on CMT prevalence [20]. Indeed, population-based studies on the epidemiology of inherited polyneuropathies are quite few [14,21,22,23] and many of them preceded the era of modern molecular diagnostics [24,25].…”
Section: Discussionmentioning
confidence: 99%
“…The prevalence of CMT in Northern Ostrobothnia was 2.5-fold higher than the median prevalence in the 10 studies included in a systematic review [20]. In 5 studies, the prevalence was in the vicinity of 10/100,000.…”
Section: Discussionmentioning
confidence: 99%
“…Worldwide, the frequency of CMT is 1 in 2500, and over the past decade, more than 40 causative genes have been identified (Barreto et al, 2016). Patients with CMT vary in severity of the disease presentation ranging from moderate physical disability to severe progressive muscle weakness (Zuchner & Vance, 2006).…”
Section: Mitofusin-2 and Diseasesmentioning
confidence: 99%
“…CMT is a demyelinating peripheral neuropathy characterised by distal muscle weakness, atrophy and sensory loss, frequently associated with foot deformity and foot drop,3 and affects approximately 10–80 per 100 000 individuals worldwide and 12 per 100 000 individuals in England 4. Individuals usually develop symptoms between 5 and 25 years.…”
Section: Discussionmentioning
confidence: 99%